The anatomical components of the cardiac outflow tract of chondrichthyans and actinopterygians - Lorenzale, Miguel; López-Unzu, Miguel A.; Rodríguez, Cristina; Fernández-Corujo, Borja; Durán-Boyero, Ana Carmen; Sans-Coma, Valentín (Cambridge University Press, 2018)
The outflow tract (OF) of the fish heart is the segment interposed between the ventricle and the ventral aorta. It holds the valves that prevent blood backflow from the gill vasculature to the ventricle. This paper offers a brief historical review of the main conceptions (anatomical composition, histological structure and evolutionary changes) about the cardiac OF components of chondrichthyans (cartilaginous fish) and actinopterygians (ray-finned fish) which have been put forward since the beginning of the nineteenth century up to the current day. Recent work on fish heart morphology has shown that the cardiac OF of chondrichthyans does not consist exclusively of the myocardial conus arteriosus (CA) as classically thought. A CA and a bulbus arteriosus, devoid of myocardium and mainly composed of elastin and smooth muscle, are usually present in cartilaginous and ray-finned fish. This is consistent with the suggestion that both components coexisted from the onset of the gnathostome radiation. There is evidence that the CA appeared in the agnathans. By contrast, the evolutionary origin of the bulbus is still unclear. It is almost certain that in all fish, both the CA and bulbus develop from the embryonic second heart field. We suggest herein that the primitive anatomical heart of the jawed vertebrates consisted of a sinus venosus containing the pacemaker tissue, an atrium possessing trabeculated myocardium, an atrioventricular region with compact myocardium which supported the atrioventricular valves, a ventricle composed of mixed myocardium, and an OF consisting of a CA, with compact myocardium in its wall and valves at its luminal side, and a non-myocardial bulbus arteriosus that connected the conus with the ventral aorta. Chondrichthyans have retained this basic anatomical design of the heart. In actinopterygians, the heart has been subject to notable changes during evolution.
Keywords: Peces - Sistema cardiovascular; Heart; Cardiac outflow tract; Conus arteriosus; Bulbus arteriosus; Anatomy; Evolution; Fish; Gnathostomes; Chondrichthyans; Actinopterygians